2014
DOI: 10.1007/s00705-014-2213-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an infectious bronchitis virus strain isolated from northern China in 2012

Abstract: This study reports the complete genome sequence of an infectious bronchitis virus (CK/CH/SD/121220, KJ128295) isolated in 2012 from Shandong Province in northern China. The genome is 27,666 nt long, comprising six genes and 5' and 3' untranslated regions. The full-length genome of the CK/CH/SD/121220 isolate had the highest nucleotide sequence identity (96.7 %) to the YX10 strain. Sites of recombination were identified in the genes 1ab, S, 5a, 5b and N, with their putative parental strains belonging to the QX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Most of the recombination breakpoints identified in isolate CK/CH/2010/JT-1 are located in these genes. To our knowledge, this recombinant virus is different from those in other reports Wu et al, 2016;Xu et al, 2016;Zhao et al, 2014). All these data indicate that the new isolate is recombined with homologous RNA recombination events from multiple template switches among QX-like, CK/CH/LSC/99I-, tl/CH/LDT3/ 03-and 4/91-type IBV strains.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Most of the recombination breakpoints identified in isolate CK/CH/2010/JT-1 are located in these genes. To our knowledge, this recombinant virus is different from those in other reports Wu et al, 2016;Xu et al, 2016;Zhao et al, 2014). All these data indicate that the new isolate is recombined with homologous RNA recombination events from multiple template switches among QX-like, CK/CH/LSC/99I-, tl/CH/LDT3/ 03-and 4/91-type IBV strains.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the IBV vaccine plays a vital role in controlling IB, it is still an epidemic across the world. IBV variants have been continuously emerging in China Xue et al, 2012;Zhao et al, 2014). The nature of the large, single-RNA genome of IBV makes the virus variable through recombination or mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of IBV genotypes and variants have been isolated in China, among which the QX-like genotype is widely prevalent there and inflicts large economic losses for farmers. The QX-like genotype was first isolated in 1998 in China, and it was considered to have a different genotype to all of the other IBVs (Li et al, 2012;Sun et al, 2011;Zhao et al, 2014). However, some studies have suggested that there is an uncertain correlation between its genotype and serotype (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-thirds of the genome encodes non-structural proteins (nsps) including the overlapping ORFs 1a and 1b, which are translated as the large polyprotein, 1ab. Protein 1ab is associated with RNA replication and transcription and can be further cleaved into 15 nsps (Zhao et al, 2014). The remaining 3 0 -end one-third of the genome encodes four major structural proteins: the spike (S) glycoprotein, the small envelope (E) protein, the membrane (M) glycoprotein, and the nucleocapsid (N) protein .…”
Section: Introductionmentioning
confidence: 99%
“…Serotype evolution and the genetic diversity of IBV are monitored by analysis of the S1 gene. The majority of QX-like IBV isolates present in the field in China had poor similarity in the S1 part of the spike protein with vaccine strains, indicating the antigenic differences and large evolutionary distances between vaccine strains and IBV field strains in China (Liu et al, 2006;Zhao et al, 2014). Despite the widespread use of live attenuated IBV vaccine (mass serotype), such as strains H120, H52, and Ma5, vaccinated chicken flocks usually fail to achieve complete protection against field virulent IBV challenge.…”
Section: Discussionmentioning
confidence: 99%